Gold(III) Complexes for Antitumor Applications: An Overview. Issue 46 (8th June 2018) - Bertrand, Benoît; Williams, Morwen R. M.; Bochmann, Manfred
Abstract: Gold(III) complexes have emerged as a versatile and effective class of metal‐based anticancer agents. The development of various types of ligands capable of stabilizing the Au III cation and preventing its reduction under physiological conditions, such as chelating nitrogen‐donors, dithiocarbamates and C^N cyclometalled ligands, has opened the way for the exploration of their potential intracellular targets and action mechanisms. At the same time, the bioconjugation of Au III complexes has emerged as a promising strategy for improving the selectivity of this class of compounds for cancer cells over healthy tissues, and recent developments have shown that combining gold complexes with molecular structures that are specifically recognized by the cell can exploit the cell's own transport mechanisms to improve selective metal uptake. Abstract : Bigger than gold : Gold(III) complexes are important potential anticancer agents. Research now focuses on the understanding of their modes of action and interactions with different potential biological targets. To try to reduce side effects of treatment with metallodrugs, bioconjugated gold complexes are being developed that allow the selective delivery to tumors.